French Baroque opera and reality TV: points of intersection - Artemieva, Vira (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. It lies in considering the production of Platée by Jean-Philippe Rameau (Garsington Opera, 2024, directed by Louisa Muller) as a vivid example of artistic dialogue between the Baroque and contemporary culture. The research highlights the unique nature of Rameau’s Platée — a work whose genre hybridity and irony constantly attract modern stage directors, inspiring innovative interpretations through the lens of today’s media formats. The main objective of the study is to identify the features of Louisa Muller’s staging of Platée and to analyze the interaction between Baroque operatic aesthetics and the phenomenon of contemporary media culture, particularly reality television and its subgenre — dating shows. The methodology includes historical-stylistic (to determine the original Baroque context of Rameau’s opera), comparative-analytical (to trace the specifics of stage interpretation, scenography, and costume design), as well as structural-functional, genre-stylistic, and intonational-dramaturgical methods (for a comprehensive examination of the work). Results and conclusions. The study interprets Platée as a synthesis of Baroque theatricality and the aesthetics of twenty-first-century media spectacle. The production reveals parallels between the emotional expressiveness of Baroque opera and the performative nature of reality TV, where the boundary between authenticity and simulation becomes blurred. Muller’s concept, based on the format of dating shows such as The Bachelor or Love Island, recontextualizes the mythological plot from Pausanias’s Description of Greece as a satire on contemporary culture of visibility and emotional exhibitionism. Through ironic play with reality, illusion, and theatricality, the production exposes the continuity between Baroque and modern conceptions of human nature. It is concluded that Rameau’s Platée in Muller’s version demonstrates the openness of Baroque opera to reinterpretation and its relevance within the dialogue between theatre and media culture.